Sabih Ailesi’nde Şiir: Araştırma ve Derleme - Abu Rached, Zakareya (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
"آل صبيح" أسرة من اسر ادبية اليت عاشت العصر العباسي، وهذه الدراسة مجعت شعر مخسة شعراء من هذه اسرة، كما درست شعرهم دراسةً فنية تكشف عن ظواهره الفنية، وهؤالء الشعراء هم: القاسم بن صبيح )عاش الشطر اول من القرن الثا اهلجري/ الثامن امليالدي(، وابنه يوسف بن القاسم )ت: 180هـ/ 796م(، وحفيداه: عبد هللا بن أمحد بن القاسم )عاش النصف اول من القرن الثالث اهلجري(، وأمحد بن أ سلمة املعروف أب بكر البغدادي )ت: 221هـ/835م(، وابن حفيده عبدهللا وامسه مد بن عبدهللا بن أمحد ويعرف أب الطيب اليوسفي )ت: 260 هــ/874م(. وقد قسمت الدرسة إلى مخسة فصول يتقدمها مدخل وتعقبها خاتمة وثبت بالمصادر والمراجع، خصصت المدخل للحديث عن المصادر اليت وردت فيها أشعار آل صبيح المعنيني ومنهج الجمع الذي التزمت به مجع شعرهم، والفصل اول لرتمجة الشعراء، والثا غراض شعرهم، والثالث للظواهر الموسيقية واللغوية، والرابع للتصوير الف، واامس للمجموع الشعري مفردًا كل مبحث فيه بشعر شاعر من الشعراء امسة. وأهم ما توصلت إليه الدراسة أن الشعراء امسة وردت أشعارهم مصادر معتبة كـ )اوراق( بكر الصو )ت: 335ه/ 947م( و)معجم الشعراء( للمرزاب )ت: 384هـ/ 994م( وغريمها من المصادر، مما يجعلنا نثق بنسبة ما مجعناه من شعرهم إليهم، وأن هؤالء الشعراء عاشوا في البلاط العباسي وكان لكل واحد منهم مكانته عند اليفة الذي عاصره وعند رجال دولته، وأن شعرهم الذي أوردته المصادر مجعكثريا من الأغراض اليت تعرض لها الشعراء عبر عصور الشعر العري، ومال إلى الأوزن الطويلة والقوافي افيفة المعتمدة على حروف الروي سهلة المخرج، ووظفت فيه احملسنات اللفظية إلضفاء موسيقى داخلية تطرب لها الأذن وتتمايل لها الأمساع، كما وظفت فيه احملسنات المعنوية إلظهار المعا وبياهنا وإحداث الدهشة المطلوبة في الشعر عند المتلقي، كما وظفت فيه وسائل التصوير الف من تشبيه واستعارة وكناية إلبراز المعا واكاة الأشياء وتصويرها التصوير الدقيق الذي يطمئن له القلب وأتنس به الروح.

“Al-i Sabîh” Abbasi döneminde yaşamış olan ailelerden biridir. Bu çalışma bu aileden beş şairin şiirini ele almış ve sanatsal açıdan özelliklerini alan bir özelliğe sahiptir. Bu beş şairin isimleri şöyledir: El-Kasım Bin Sabîh (Hicri 2. Yüzyılın başlarında/Miladi 8. yüzyılda yaşamıştır.), oğlu Yusuf bin El-Kasım (v. 180/796), iki torunu Abdullah bin Ahmed bin El-Kasım (Hicri 3. Yüzyılın ilk yarısında yaşamıştır.) ve Ebu Bekir El-Bağdadi olarak bilinen Ahmed bin Ebi Seleme (v. 221/835), torunu Abdullah’ın oğlu Ebu’t-Tayyib El-Yusufi olarak da bilinen Muhammed bin Abdullah bin Ahmed (v. 260/874). Bu çalışma Giriş, 5 bölüm ve Sonuç kısımlarına ayrılır ve son olarak kaynakça bölümünden oluşur. Giriş bölümünü adı geçen Al-i Sabîh ailesi mensuplarının şiirlerinin geçtiği kaynaklar hakkında ve şiirlerini derlerken kullandığım yönetim hakkında konuşmaya ayırdım. Birinci bölümü şairlerin biyografilerine, ikinci bölümü şiir yazmadaki amaçlarına, üçüncü bölümü şiirlerindeki müziksel ve dilsel olgulara, dördüncü bölümü sanatsal betimlemeye, beşinci bölümü ise 5 şairden her birinin bir şiiri tek bir konuyu teşkil edecek şekilde düzenledim. Araştırmamızın ulaştığı sonuçların en önemlisi, 5 şairin şiirlerinin Ebu bekir El-Savli’nin eseri olan (v. 335/947) “el-Evrak”, El-Merzebani’nin eseri olan (v. 384/994) “Mucemu’ş-Şuara” gibi güvenilir kaynaklarda geçmiş olmasının doğrulanmasıdır. Bu durum topladığımız şiirlerin onlara ait olduğuna dair güvenimizi güçlendirmektedir. Bu şairler Abbasi toprağında yaşamış ve hepsi zamanının Halifesi ve devlet adamları tarafından sevilirlermiş. Onların kaynaklarda geçen şiirleri Arapların tarih boyunca karşılaştığı birçok olayı içerir. Aynı zamanda şiirlerinde uzun vezinlere, telaffuzu kolay revî harflerine dayanan hafif kafiyelere yer verirler. Şiirlerinde kulağa hoş gelecek iç müzik ortaya çıkaran lafzî süsleme sanatları ve anlamları ortaya çıkarmak, açıklamak ve şiiri okuyan kişide istenilen hayreti bırakması için mânevî süsleme sanatları kullanılmıştır. Aynı şekilde anlamları daha iyi açıklamak, birtakım şeyleri birbirine benzetmek ve kalbin rahatlayacağı, ruhun hoşuna gidecek şekilde titiz betimleme için teşbih, istiare ve kinaye gibi betimleme araçları kullanılmıştır.

The Sabeeh family is one of the literary families that thrived during the Abbasid era. This study compiles the poetry of five poets from this family and provides a detailed analysis of their artistic expressions. The featured poets are Al-Qasim bin Sabeeh (who lived in the first half of the 2nd century AH/8th century CE), his son Yusuf bin Al-Qasim (deceased 180 AH / 796 CE), and his grandsons: Abdullah bin Ahmed bin Al-Qasim, who lived in the first half of the 3rd century AH, Ahmed bin Abi Salama, also known as Abu Bakr Al-Baghdadi (deceased 213 AH/828 CE), and Abdullah's son, Muhammad bin Abdullah bin Ahmed, known as Abu Al-Tayyib Al-Yousefi (deceased 260 AH/874 CE). The study is divided into five chapters, with an introduction and a conclusion, supported by references and sources. The introduction discusses the sources in which the poems of the Sabeeh family were found and the methodology used in collecting their poetry. The first chapter is dedicated to the biographies of the poets, while the second focuses on their poetic themes. The third chapter delves into the musical and linguistic aspects of their poetry, and the fourth explores their artistic imagery. The fifth chapter presents the entire poetic collection, with each section dedicated to the work of one of the five poets. The most significant findings of this study are that the poems of these five poets were documented in reputable sources such as "Al-Awraq" by Abu Bakr Al-Souli (deceased 335 AH/947 CE) and "Mu'jam Al-Shu'ara" by Al-Marzubani (deceased 384 AH/994 CE), among others. This gives us confidence in attributing the collected poetry to them. Furthermore, these poets lived in the Abbasid court, and each of them held a special status among the caliph and his associates. Their poetry, as documented in these sources, encompasses a wide range of themes, many of which are common throughout various eras of Arabic poetry, and utilizes long meters and light rhymes based on easily pronounced letters, employing phonetic embellishments to create internal musicality that delights the ear and captivates the mind. Additionally, they employed semantic enhancements to convey and express meanings effectively, creating the desired impact in poetry when presented to the audience. They also employed various artistic techniques, such as simile, metaphor, and allegory, to illustrate and simulate objects with precise and detailed imagery that soothes the heart and resonates with the soul.
Keywords: شعراء العصر العباسي; آل صبيح; جماليات الشعر; Abbasi Dönemi Şairleri; Al-i Sabîh; Şiirin Güzellikleri; Abbasid-Era Poets; Sabeeh Family; Poetic Aesthetics